2016
DOI: 10.1177/0022022116658260
|View full text |Cite
|
Sign up to set email alerts
|

Confucian Culture Still Matters

Abstract: Zhongyong thinking (Doctrine of the Mean) is a traditional Confucius interpersonal style with emphasis on interpersonal harmony and connection. In contemporary society, is Zhongyong thinking beneficial to, or has Zhongyong thinking become an old-fashioned idea with trivial or even detrimental influence on mental health? The current study explored the relationship of Zhongyong thinking and mental health measures in two studies. Study 1 was a cross-sectional survey involving a large representative sample of 8,17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 46 publications
3
33
0
1
Order By: Relevance
“…This study further demonstrated that Zhongyong thinking was negatively and moderately correlated with depressive symptoms, and negatively and mildly correlated with anxiety symptoms. This result was consistent with previous findings (Zhan et al, 2013;Yang et al, 2016). Zhongyong thinking is therefore related to emotional distress of Chinese college students.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This study further demonstrated that Zhongyong thinking was negatively and moderately correlated with depressive symptoms, and negatively and mildly correlated with anxiety symptoms. This result was consistent with previous findings (Zhan et al, 2013;Yang et al, 2016). Zhongyong thinking is therefore related to emotional distress of Chinese college students.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the diathesis-stress model, individuals with some personality traits, such as poor self-esteem (Nguyen et al, 2019), low self-directedness and cooperativeness (Lim et al, 2018), low agreeableness (Roman et al, 2019), and high perfectionism (Bußenius and Harendza, 2019), may predispose them to develop more depression and anxiety symptoms. Results from two cross-sectional studies demonstrated that Chinese adults with high level of Zhongyong thinking style had few depressive and anxiety symptoms (Zhan et al, 2013;Yang et al, 2016). Moreover, Yang et al (2016) conducted a longitudinal study and found that Chinese college student's depressive symptoms could be relieved through the training of Zhongyong thinking in group psychotherapy.…”
Section: Zhongyong Thinking and Emotional Distressmentioning
confidence: 99%
See 2 more Smart Citations
“…Protože lidé uplatňující myšlení střední cesty mají vyšší sebehodnocení a životní spokojenost a skórují níže ve škálách úzkosti a deprese, zkusili Yang et al (2016), jestli jeho trénink zvýší účinnost klasické psychoterapie. Jednu skupinu studentů s depresivními potížemi nechali podstoupit standardní podpůrnou skupinovou terapii.…”
Section: Zhong Yongunclassified